4(5x+3)-4x=-6(7-2x)+2x-5+2x

Simple and best practice solution for 4(5x+3)-4x=-6(7-2x)+2x-5+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5x+3)-4x=-6(7-2x)+2x-5+2x equation:


Simplifying
4(5x + 3) + -4x = -6(7 + -2x) + 2x + -5 + 2x

Reorder the terms:
4(3 + 5x) + -4x = -6(7 + -2x) + 2x + -5 + 2x
(3 * 4 + 5x * 4) + -4x = -6(7 + -2x) + 2x + -5 + 2x
(12 + 20x) + -4x = -6(7 + -2x) + 2x + -5 + 2x

Combine like terms: 20x + -4x = 16x
12 + 16x = -6(7 + -2x) + 2x + -5 + 2x
12 + 16x = (7 * -6 + -2x * -6) + 2x + -5 + 2x
12 + 16x = (-42 + 12x) + 2x + -5 + 2x

Reorder the terms:
12 + 16x = -42 + -5 + 12x + 2x + 2x

Combine like terms: -42 + -5 = -47
12 + 16x = -47 + 12x + 2x + 2x

Combine like terms: 12x + 2x = 14x
12 + 16x = -47 + 14x + 2x

Combine like terms: 14x + 2x = 16x
12 + 16x = -47 + 16x

Add '-16x' to each side of the equation.
12 + 16x + -16x = -47 + 16x + -16x

Combine like terms: 16x + -16x = 0
12 + 0 = -47 + 16x + -16x
12 = -47 + 16x + -16x

Combine like terms: 16x + -16x = 0
12 = -47 + 0
12 = -47

Solving
12 = -47

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 10+x=-11 | | -25+x=x+27 | | 6x-6=90 | | 4y-26-3y=16-20 | | 3x-6-5x=9+7 | | 4+5q=14 | | 7c*7e= | | x^2-24x+144=49 | | 100=x+0.2x | | 8-x=x+10 | | 3x-6-5=9+7 | | 2x+8=4x-18 | | x+x+1+x+2+x+3=30 | | x-(-5)=3 | | n+n+2+n+4=66 | | (18x-8)=(6x+4) | | 8(x-3)=23-2x | | 7x-(x-3)=6 | | .5(b)(2b+8)=21 | | 2g+4(3-g)=5g+19 | | x+x+1+x+2+x+3=-15 | | 4x+25=2x+49 | | 4x+36y=-12graph | | 2x+8(x-2)=4x-3(3-2x)-7 | | 3+3x=-7+x | | 6x-3(2x-4)+1=13 | | 15-4x+30=7-x | | 4+12+x=4+6+2x | | -0.01x^2+1.8x-106=0 | | 3+55x=33x+9 | | 4x+7=6x-19 | | (5y+9)+y= |

Equations solver categories